OFFICE ROTATION POLICY IN DULUPI VILLAGE DULUPI DISTRICT: KEBIJAKAN ROTASI APARAT DI DESA DULUPI KECAMATAN DULUPI - lasmin hasan; Imam Mashudi; Maman Musa (Jurnal Ilmu Manajemen dan Bisnis, 2023)
The aims of this research are 1) To find out the impact of the officer rotation policy which is not in accordance with the applicable regulations. 2) To analyze the job rotation policy that affects the work productivity of village officials. The research that will be conducted uses a descriptive qualitative approach. The data sources used in this research are primary data sources, namely data sources that directly provide data to data collectors. Data collection methods used were interviews, observation and documentation. Data analysis techniques used were data analysis techniques according to Miles and Huberman. With data analysis, namely data reduction, data display and conclusion drawing/verification. The results of the study are 1) Internal impact is namely the Village Officials are no longer performing optimally, feel uncomfortable with the new job because they still have to adapt and learn more about the main duties and functions of the new position. In fact, they are often not in harmony with other village officials. The external impact is that there are people who feel that service to the community due to this rotation has decreased, and even their social relations have changed a lot. 2) The rotation policy for village officials greatly affects the work productivity of village officials in the Dulupi Village Government. It has not been able to support the capacity building of village officials in the Dulupi Village Government.